1999
DOI: 10.1111/j.1475-4754.1999.tb00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone Porosity and the Use of Mercury Intrusion Porosimetry in Bone Diagenesis Studies*

Abstract: Porosiry measurements made on archaeological bones have revealed very close relationships between changes in the porosity, remaining protein content and mineral alterations. The results have important implications for models that attempt to quantih the rates and extent of chemicul reaction between bone and its geochemical environment. We report here on a novel application of an established technique, mercury intrusion porosimetry, to investigate in more detail the pore size distribution of archaeological bones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 19 publications
3
41
0
1
Order By: Relevance
“…The fabric of the well-preserved bones in general appears more uniform, while the bones that contain little collagen appear more variable and porous. This is what we would expect from previous studies of diagenetic alteration of bone, which found that diagenesis leads to an increase in the porosity of bone (Nielsen-Marsh and Hedges 1999;Hedges 2002).…”
Section: Imagessupporting
confidence: 87%
“…The fabric of the well-preserved bones in general appears more uniform, while the bones that contain little collagen appear more variable and porous. This is what we would expect from previous studies of diagenetic alteration of bone, which found that diagenesis leads to an increase in the porosity of bone (Nielsen-Marsh and Hedges 1999;Hedges 2002).…”
Section: Imagessupporting
confidence: 87%
“…The very small pores visible in Figure 3 correspond to the increased porosity between 0.007 and 0.1 µm diameter, at or below, the scale of the collagen fibril (0.1 µm diameter) (Weiner & Traub, 1986;Traub et al, 1989;Sarathchandra et al, 1999) previously reported for deproteinated bone (Holmes et al, 1964;Nielsen-Marsh & Hedges, 1999). Imaging of these very small pores was achieved using FEG-SEM, which has a very small, tight beam with low aberration and correspondingly small excitation volume in the sample.…”
Section: Comparison Of Archaeological Bones Using Hgipmentioning
confidence: 98%
“…In this paper we explore the application of an alternative approach, mercury intrusion porosimetry (HgIP), first reported by Nielsen-Marsh and Hedges (1999). This technique has advantages over the water sorption approach previously used to examine archaeological bone because it permits a more rapid and detailed assessment of the pore size distribution, although unlike water adsorption it cannot be applied to measure pores of <10 nm (0.01 µm).…”
Section: Introductionmentioning
confidence: 97%
“…These processes are complex because they are multi-factorial, non-linear in time and operate in a heterogeneous way and at different structural levels (Hedges 2002;Budd et al 2000;Kohn et al 1999;Reiche et al 2002aReiche et al , 2003Dauphin and Williams 2004;Geigl 2002;O'Connor et al 2011;Godfrey et al 2002;Albéric et al 2014;Large et al 2011;Baud and Tochon-Danguy 1985;Jans et al 2004;Nielsen-March and Hedges 1999;Nielsen-Marsh et al 2007;Collins et al 2002).…”
Section: Introductionmentioning
confidence: 99%